2010
DOI: 10.1007/978-90-481-9485-8_20
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Congenital Anomalies in Europe

Abstract: EUROCAT (European Surveillance of Congenital Anomalies) is the network of population-based registers of congenital anomaly in Europe, with a common protocol and data quality review, covering 1.5 million annual births in 22 countries. EUROCAT recorded a total prevalence of major congenital anomalies of 23.9 per 1,000 births for 2003-2007. 80% were livebirths. 2.5% of livebirths with congenital anomaly died in the first week of life. 2.0% were stillbirths or fetal deaths from 20 weeks gestation. 17.6% of all cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
421
5
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(489 citation statements)
references
References 26 publications
45
421
5
18
Order By: Relevance
“…24 The incidence of major congenital malformations was 1/47 (2.12%) which is in line with the series of Desmyttere et al 25 and with the Eurocat figure of 23.9/1000. 26 The success figures of PGD should also be compared with what is known on the outcome of natural conceptions in fertile carriers. Sugiura-Ogasawara et al 27 found that of 72 rcp carriers, ascertained by For the successful PGD couples, their first PGD child was mostly born within 1.5 years after the work-up for PGD.…”
Section: Discussionmentioning
confidence: 99%
“…24 The incidence of major congenital malformations was 1/47 (2.12%) which is in line with the series of Desmyttere et al 25 and with the Eurocat figure of 23.9/1000. 26 The success figures of PGD should also be compared with what is known on the outcome of natural conceptions in fertile carriers. Sugiura-Ogasawara et al 27 found that of 72 rcp carriers, ascertained by For the successful PGD couples, their first PGD child was mostly born within 1.5 years after the work-up for PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Many fetal abnormalities may only be noted after delivery 1 . If fetal abnormality is unexpected there is often only one chance to examine a fetus for dysmorphic features and to decide on appropriate investigation.…”
Section: Fetal Examinationmentioning
confidence: 99%
“…Analysis of data from European population-based congenital anomaly registers reported a malformation rate of 29.3 per 1000 births 1 . Eighty percent of these were in live births whereas 17% were observed in fetuses terminated after ultrasound diagnosis of fetal abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…diabetes | congenital heart defects | heterotaxia | left-right axis C ongenital heart defects (CHDs) are among the most common birth defects in humans, affecting 0.8-1.16% of live births (1,2). Such defects are not necessarily caused by genetic alterations, with epidemiological studies having revealed that various modifiable factors increase the risk of specific types of CHD (1,3).…”
mentioning
confidence: 99%